Comparative analysis of modelling adequacy of the nonstationary traffic in telecommunication networks - Guziy, M. M.; Ignatov, V. O.; Zijuan, Wu (Problems of Informatization and Control, 2007)
In paper results of the comparative analysis of modeling adequacy of the nonstationary traffic in telecommunication networks are given. For optimum modeling dynamics of the traffic metrics of spaces Euclid and Gilbert are used. The algorithm and a technique of verification of optimum models are developed. It is shown, that modeling of the nonstationary traffic in space Gilbert is preferable as gives more exact models. Theoretical positions are illustrated by numerical examples and diagrams with use of system MathCAD